Kleinhospitine E and Cycloartane Triterpenoids from Kleinhovia hospita - Rahim, Abdul (J Nat Prod, 2018)
A novel cycloartane triterpenoid alkaloid, kleinhospitine E (1), six new cycloartane triterpenoids (2−7), three known cycloartane triterpenoids (8−10), and taraxerone (11) were isolated from a methanol extract of Kleinhovia hospita. Their structures were elucidated by 1D-and 2D-NMR spectroscopy as well as HRMS analysis. The absolute configurations of all isolated compounds were determined from their ECD spectra by comparison with theoretical values. Kleinhospitine E (1) is the first cycloartane alkaloid possessing an unusual γ-lactam with an oxopropylidene side chain. Compounds 2, 3, and 6 were assigned as cycloartane triterpenoids with a 9α,10α-cyclopropyl ring, which is found rarely among naturally occurring compounds, while 4 and 5 were established as isomers of compound 3 containing a 21,23-diacetal side chain. Biological evaluation revealed that compounds 4 and 9 exhibited more potent antiproliferative activities against a multidrug-resistant tumor cell line compared with its parent chemosensitive cell line. Furthermore, compound 6 exhibited submicromolar anti-HIV activity.